(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this era of the digital world, handling digital data with a secure passion is more important. At the height of maximum interest with the attainment of the data confidentiality with the miniature information is the tedious and most challenging concern of the system with the data handling and operating in the real-time environment. With the latest data confidentiality security model, such as image encryption over the communication networks in the distributed data environment, advanced hacking efforts such as cropping attack, brute force, differential, mathematical, and many more need to be addressed. In terms of bit scrambling, the security function plays a vital role in the pixel-based approach with minimum pixels are followed in the current security model for a better correlation with the available pixels with the continued higher runtime complexity. In this research paper, along with the DNA encoding process, an efficient image cryptographic technique is shown with the reduced runtime complexity. The discussion in the article begins with the chaotic sequence EIIS (Efficient Image Information Scrambling) method. Progressed with the DNA (Deoxyribo Nucleic Acid) encoding is done with the data for resistance against different kinds of attacks by considering the suitable parameters from the existing security models.